Organizing of images custom filters testing for «the ultra fast X-ray imaging of scientific processes with on-line assessment and data-driven process control» (UFO) - Shkarin R. V. (Section VII: Informatics and Control in Engineering Systems, 2012)
Заглавие с титульного листа